Loss of Consciousness in Nasopharyngeal Carcinoma with Brainstem Infiltration - Tiara Aninditha; Ikhlas Rahmadi; Ferucha Moulanda; Ardhi Rahman Ahani; Radius Kusuma; Henry Riyanto Sofyan; Irma Savitri (Acta Neurologica Indonesia, 2025)
Introduction: Nasopharyngeal carcinoma (NPC) is prone to intracranial infiltration in advanced stages due to its proximity to the skull base, despite the protective bony structures. Loss of consciousness in NPC patients with brainstem involvement should be distinguished from other causes. Case Report: A 70-year-old man developed progressive symptoms, including left otalgia and trismus, within eight months before admission. CT revealed a nasopharyngeal mass infiltrating the medullary and pontine cisterns, confirmed as nonkeratinized NPC from biopsy. One month prior, he underwent tracheostomy for airway obstruction. Ten days before admission, he experienced nausea, vomiting, and altered consciousness. During hospitalization, severe hyponatremia was detected and confirmed as the main etiology, further proven by the fact that the patient only regained consciousness after hypertonic saline infusion while being unresponsive after prior dexamethasone administration. After four days, he was discharged with plans for chemotherapy and radiotherapy. Discussion: Brainstem infiltration in NPC is rare, even in advanced stages, due to the protective skull base. However, intracranial spread can occur via foramina or direct bony destruction. Loss of consciousness in NPC patients with suspected brainstem infiltration requires careful evaluation, as non-tumoral causes like hyponatremia should be considered. Tumor-induced malnutrition, impairing mastication and intake, may contribute to electrolyte imbalances. Conclusion: In NPC patients with brainstem infiltration, loss of consciousness should not be immediately attributed to direct tumor invasion. Other treatable causes, such as hyponatremia, must be promptly detected to ensure appropriate management.